Enhancing the Ability in Writing Narrative Text of Junior High School through Picture Series - Cicih Nuraeni (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2019)
The objective of this study is to find out whether the use of picture series significantly improves the achievement on writing narrative text of the eighth grade students of Junior High School. The subject of this study is the eighth grade students of SMP Negeri 76 Jakarta. The sample of this study is the students VIII-4 consisting 30 students. The method of this research is descriptive qualitative method.. The technique for collecting the qualitative data was gathered through students’ writing text and observation sheet. Qualitative data showed that the students were interested in using pictures as the learning media in writing narrative text. From the findings can be seen that student’s narrative writing is found improved through picture series. Students’ responses toward the use of picture series activity in EFL writing classroom were mostly positive. It can be concluded that picture series was an interesting alternative. Under certain condition, it was said more intensive than other approach and this gives them chances to be aware on their mistakes in writing. Overall, the students’ revised version drafts are more developed. As suggested by researchers and teachers, picture series should be implemented thoroughly, carefully, and well-planned.